Innovation to Improve Service Quality Based on Classes (Study on BPJS Kesehatan Using Communities In The General Hospital, Depati Hamzah, Pangkalpinang City): - Suwaibah Putri (International Journal of Regional Innovation, 2023)
According to Law Number 25 of 2009 concerning Public Services. Public service is an activity or a series of activities in the context of fulfilling service needs in accordance with statutory regulations for every citizen and resident for goods, services and/or administrative services provided by public service providers. The purpose of this research is toTo find out the quality of services provided to social classes in the BPJS Health user community. This study uses public service theory according to Lijan Poltak Sinambela regarding public service. This study used a descriptive qualitative method. The technique of determining the informants in this study was carried out by means of a purposive sampling technique by means of interviews and documentation. The results of the study show that the quality of public services in BPJS classes at the general hospital in the Depati Hamza area of ​​Pangkalpinang City can be said to be good, namely on the principles of transparency and accountability. Based on the principle of equality and participatory which must also be fulfilled to improve the quality of service.